Mãos que constroem: a incorporação de apenados como prática de cidadania corporativa em uma empresa de construção civil de Fortaleza - Rocha, Virna Fernandes Távora (2014)
To make it possible for the former prisioners to return to social life, with no relapses, is one of the punishment’s goals. As a result, the responsible entities are in a constant search to provide it to their beneficiaries. The Department of Justice and Citizenship (Sejus), in Ceará, has developed numerous projects and business partnerships with this result in mind. With the events held in Brazil in the years 2013, 2014 and 2016, the National Council of Justice (CNJ), along with FIFA, saw the opportunity for a rehabilitation path. This way, it was determined that the organizations involved with the construction work related to these events should hire convicts and ex-convicts as your workforce. Consequently, Sejus, in order to meet this demand and establish the connection between companies and convicts, created the program “Mãos que Constroem” (Hands that Build), where the main purpose is to encourage the professionalization of their beneficiaries. Thus, this initiative is part of the theme Corporate Social Responsibility (CSR), which increasingly becomes important on the context of organizations. The RSC has a range of denominations and groups a series of concepts, among them is the Corporate Citizenship (CC). It establishes that a business organization has the role of checking the rights of individual citizens, Corporate Citizenship proposes a new challenge to businesses. Social contributions, such as the hiring of inmates in the prison system, are characterized as practices of corporate citizenship. To investigate the company’s actions, Mirvis and Googins’s model of corporate citizenship (2006) was used as the main reference model. From this model it will be possible to determine the intention of their corporate citizenship when hiring convicts. From this model will be possible to analyze the corporate citizenship stage of a company in the construction sector that incorporates inmates of the prison system in the labor market. In order for this to happen, this study is classified as a qualitative research, based on a descriptive study. As a method of qualitative data collection, interviews and desk research were used. A field survey was conducted in a construction company, focusing on the managers responsible for the convicts, and the prison guards themselves. A single case study was also conducted. As the main source of data collection were used interviews. For this study, three interviews protocols were used. From this, it was concluded that the company is focusing its development on increasing its participation on social issues, aiming sustainability as a final goal. Work, education and specific qualifications for the job were the rehabilitation strategies chosen by Galvão Engenharia. These three strands seem to hold different meanings for the convicts, highlighting, in order of importance, the work, the qualification and, finally, education, which was not given the rightful importance. In this research, the relationship between Sejus, Galvão Engenharia and convicts was highlighted. Galvão Engenharia interacts with Sejus to give job opportunity, qualification and education for the inmates, positioning itself in a process that involves citizenship in its corporate agenda.